Recent Advances in Translational Magnetic Resonance Imaging in Animal Models of Stress and Depression - McIntosh, Allison L.; Gormley, Shane; Tozzi, Leonardo; Frodl, Thomas; Harkin, Andrew (Frontiers in Cellular Neuroscience, 2017)
Magnetic resonance imaging (MRI) is a valuable translational tool that can be used to investigate alterations in brain structure and function in both patients and animal models of disease. Regional changes in brain structure, functional connectivity and metabolite concentrations have been reported in depressed patients, giving insight into the networks and brain regions involved, however preclinical models are less well characterised. The development of more effective treatments depends upon animal models that best translate to the human condition and animal models may be exploited to assess the molecular and cellular alterations that accompany neuroimaging changes. Recent advances in preclinical imaging have facilitated significant developments within the field, particularly relating to high resolution structural imaging and resting-state functional imaging which are emerging techniques in clinical research. This review aims to bring together the current literature on preclinical neuroimaging in animal models of stress and depression, highlighting promising avenues of research towards understanding the pathological basis of these hugely prevalent disorders.